Potential for Targeting Myeloid Cells in Controlling CNS Inflammation - Ifergan, Igal; Miller, Stephen D. (Frontiers in Immunology, 2020)
Multiple Sclerosis (MS) is characterized by immune cell infiltration to the central nervous system (CNS) as well as loss of myelin. Characterization of the cells in lesions of MS patients revealed an important accumulation of myeloid cells such as macrophages and dendritic cells (DCs). Data from the experimental autoimmune encephalomyelitis (EAE) model of MS supports the importance of peripheral myeloid cells in the disease pathology. However, the majority of MS therapies focus on lymphocytes. As we will discuss in this review, multiple strategies are now in place to target myeloid cells in clinical trials. These strategies have emerged from data in both human and mouse studies. We discuss strategies targeting myeloid cell migration, growth factors and cytokines, biological functions (with a focus on miRNAs), and immunological activities (with a focus on nanoparticles).